Systemic hypersensitivity reaction to Omnipaque radiocontrast medium: a case of mini‐DRESS. Issue 4 (21st February 2016) - George, Christina; Sears, Alison; Selim, Abdel‐Ghani; Walsh, Sarah; Creamer, Daniel
Key Clinical Message: Drug reaction with eosinophilia and systemic symptoms (DRESS) is a delayed drug reaction defined by physical signs and laboratory parameters. Mini‐DRESS is a new entity, in cases that display some but not all features of DRESS. Cases of mini‐DRESS have a less protracted course, and respond well to systemic corticosteroid treatment. Abstract : Drug reaction with eosinophilia and systemic symptoms (DRESS) is a delayed drug reaction defined by physical signs and laboratory parameters. Mini‐DRESS is a new entity, in cases that display some but not all features of DRESS. Cases of mini‐DRESS have a less protracted course, and respond well to systemic corticosteroid treatment.